The Role of Halal Awareness in Mediating the Influence of Digital Content and Influencers on the Intention to Purchase Halal Food Products among Tadulako University Students - Bayu Permana; Syamsul Bahri Daeng Parani; Maskuri Sutomo; Sri Wanti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Objective: This study examines the influence of digital content and influencer marketing on halal food purchase intention among university students, with halal awareness acting as an intermediary variable. Methods: A quantitative cross-sectional survey was conducted among 301 undergraduate students at Tadulako University, Indonesia. Data were collected through a structured online questionnaire using a validated measurement scale. Data analysis was conducted using Partial Least Squares-Based Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software, implementing a two-stage assessment of the measurement and structural models. The mediation effect was tested using bootstrapping with 5,000 resamplings, and predictive validity was tested through the PLS-Predict procedure. Results: The findings indicate that digital content and influencer marketing have a positive and significant influence on both halal awareness and purchase intention. Halal awareness also has a positive influence on purchase intention and partially mediates the relationship between digital marketing variables and purchase intention. Implications: This study confirms that halal awareness is the main mechanism linking digital marketing strategies with halal consumption behavior, and provides practical guidance for halal food businesses in reaching young Muslim consumers